From Classroom To Brand: How Organizational Culture And Affective Commitment Foster Employer Branding Through Employee Engagement In Buddhist Foundation Schools In Indonesia - Kornelia Mawarni; Lianto - Lianto (Universitas Riau Kepulauan, 2026)
This study examines how organizational culture (OC) and affective commitment (AC) influence employer branding (EB) through the mediating role of employee engagement (EE) among teachers and administrative staff of a Buddhist-affiliated multi-level educational foundation in Singkawang, West Kalimantan, Indonesia. Employer branding research has concentrated almost exclusively on corporate settings and higher education institutions, leaving primary and secondary schools—particularly those operating within faith-based, non-metropolitan contexts—largely unstudied. Drawing on Job Demands–Resources theory, Social Exchange Theory, and Signaling Theory, this study proposes an indirect-only mediation model in which OC and AC shape EB exclusively through EE. A census survey of the entire organizational population (N = 52) was conducted and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0. All five hypotheses were supported. Organizational culture positively influenced employee engagement (β = 0.267, p = 0.019), while affective commitment emerged as the dominant engagement driver (β = 0.600, p < 0.001). Employee engagement, in turn, strongly predicted employer branding (β = 0.717, p < 0.001). Both indirect effects were significant: OC → EE → EB (β = 0.191, p = 0.021) and AC → EE → EB (β = 0.430, p < 0.001), confirming indirect-only mediation. The model explained 70.5% of the variance in employee engagement and 51.3% in employer branding. These findings extend employer branding theory into faith-based primary and secondary schools, identify employee engagement as the pivotal internal brand-building mechanism, and offer school leaders actionable guidance: cultivating a values-driven culture and deepening teachers' affective bonds are the most effective pathways to strengthening institutional reputation as an employer.